O problema da escolha entre teorias : um diálogo entre o pensamento kuhniano e a teoria de duplo processamento - Tiago Barbosa S. Thiago (2016)
This dissertation aims to analyze the problem of theory choice by taking as a starting point the context raised by the historicist reading, focusing especially on the complications that result from deliberations involving different paradigms. Firstly, a critical view regarding scientific choices in history is presented, with reference to Thomas Kuhn‟s The Structure of Scientific Revolutions. Secondly, after highlighting a series of problems that were left unsolved by previous accounts, this dissertation follows Kuhn‟s paper “Objectivity, Value Judgment and Theory Choice” in order to explore the objective foundations that support theory choice, namely, cognitive values. However, a brief investigation will make it clear that cognitive values are sometimes inaccurate and insufficient. Thus, by noting the impossibility of finding an adequate general decision algorithm, this work focuses on a research regarding psychological aspects of choice, and, in particular, on the nature of an individual scientist‟s algorithm. We thus consider the fact that the scientist is always involved in a social context, one that dialogues with the individual as historically constituted and subjectively distinct. For this last task, we make use of dual process theory as well as concepts that have been reworked by it, such as those of creativity and motivation.